2021
DOI: 10.1021/acssuschemeng.1c03730
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Fusion Protein to Facilitate Calcium Carbonate Mineralization on Insoluble Polysaccharide for Efficient Biocementation

Abstract: Biomineralization is a process of mineral formation in living organisms. Compared with nonbiogenic minerals, biominerals can be defined as organic−inorganic hybrid materials that have excellent physical and optical properties. In the current study, an artificial protein mimicking the outer shell of crayfish, composed of CaCO 3 , chitin, and proteins, was developed to facilitate organic−inorganic hybrid material formation by precipitation of calcium carbonate on the chitin matrix. The fusion protein (CaBP-ChBD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…[ 264 ] Nakashima et al synthesized organic–inorganic hybrid materials composed of chitin, proteins, and calcium carbonate ( Figure a). [ 265 ] The fusion protein is formed by the calcite‐binding peptide and chitin‐binding domain, whereby calcium carbonate can adsorb and grow on the sites of the chitin matrix. Twisted stacking or symmetry‐breaking alignment is a common strategy to optimize the mechanical performance of composites.…”
Section: Applications Of Biomimetic Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 264 ] Nakashima et al synthesized organic–inorganic hybrid materials composed of chitin, proteins, and calcium carbonate ( Figure a). [ 265 ] The fusion protein is formed by the calcite‐binding peptide and chitin‐binding domain, whereby calcium carbonate can adsorb and grow on the sites of the chitin matrix. Twisted stacking or symmetry‐breaking alignment is a common strategy to optimize the mechanical performance of composites.…”
Section: Applications Of Biomimetic Materialsmentioning
confidence: 99%
“…Reproduced with permission. [ 265 ] Copyright 2021, American Chemical Society. b–d) Preparation of the nanoparticles‐incorporated artificial nacre with excellent toughness: b) artificial nacre, c) nacre–mimetic structure, and d) combination of aragonite platelet with nanoparticles.…”
Section: Applications Of Biomimetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shell of mussels is composed of CaCO 3 particles, protein, and chitin, which is a multistructure composite architecture. [71][72][73][74] In addition to the outermost cuticle, the prismatic layer in the middle and the nacre layer in the inner layer are the main part of mechanical energy dissipation. [75][76][77] Nacre is a typical layered structure, which can deflect cracks and prevent crack propagation, so as to provide toughness and dissipate mechanical energy.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrated a novel approach for fabricating a hybrid silica-coated chitosan gel incorporating enzymes. To immobilise silicatein on the chitosan gel, we employed a chitin-binding module (ChBD), 26 which is known to bind chitosan gel. Although silicatein is an aggregative enzyme in water, we successfully solved this problem by introducing highly soluble proteins such as ProS2 21 and InaKC.…”
mentioning
confidence: 99%